Describing the natural history of clinical, biochemical and radiological outcomes of children with familial partial lipodystrophy type 2 (FPLD2) from the United Kingdom: A retrospective case series. (17th August 2022) - Zhong, Zhu Xuan; Harris, Julie; Wilber, Ellen; Gorman, Samantha; Savage, David B.; O'Rahilly, Stephen; Stears, Anna; Williams, Rachel M.
Abstract: Context: Familial partial lipodystrophy type 2 (FPLD2) results from autosomal dominant mutations in the LMNA gene, causing lack of subcutaneous fat deposition and excess ectopic fat accumulation, leading to metabolic complications and reduced life expectancy. The rarity of the condition means that the natural history of FPLD2 throughout childhood is not well understood. We report outcomes in a cohort of 12 (5M) children with a genetic diagnosis of FPLD2, under the care of the UK National Severe Insulin Resistance Service (NSIRS) which offers multidisciplinary input including dietetic, in addition to screening for comorbidities. Objective: To describe the natural history of clinical, biochemical and radiological outcomes of children with FPLD2. Design: A retrospective case note review of children with a genetic diagnosis of FPLD2 who had been seen in the paediatric NSIRS was performed. Patients: Twelve (5M) individuals diagnosed with FPLD2 via genetic testing before age 18 and who attended the NSIRS clinic were included. Measurements: Relationships between metabolic variables (HbA1c, triglycerides, fasting insulin, fasting glucose and alanine transaminase [ALT]) across time, from first visit to most recent, were explored using a multivariate model, adjusted for age and gender. The age of development of comorbidities was recorded. Results: Three patients (all female) developed diabetes between 12 and 19 years and were treated with Metformin. One female has hypertrophic cardiomyopathy and four (1M) patients developed mild hepatic steatosis at a median [range] age of 14(12–15) years. Three (1M) patients reported mental health problems related to lipodystrophy. There was no relationship between biochemical results and age. Patients with diabetes had higher concentrations of ALT than patients who did not have diabetes, adjusted for age, gender and body mass index standard deviation scores. Conclusions: Despite dietetic input, some patients, more commonly females, developed comorbidities after the age of 10. The absence of relationships between biochemical results and age likely reflects a small cohort size. We propose that, while clinical review and dietetic support are beneficial for children with FPLD2, formal screening for comorbidities before age 10 may not be of benefit. Clinical input from an multidisciplinary team including dietician, psychologist and clinician should be offered after diagnosis.